Detection of an untyped strain of bovine respiratory syncytial virus in a dairy herd - Ingrid Bortolin Affonso; Andressa Souza; Matheus Cavalheiro Martini; Márcia Mercês Aparecida Bianchi dos Santos; Fernando Rosado Spilki; Clarice Weis Arns; Samir Issa Samara (Semina: Ciências Agrárias, 2014)
Bovine respiratory syncytial virus (BRSV) causes important lower respiratory tract illness in calves. According to F and G proteins genetic sequences, three BRSV subgroups have been reported and characterized in several countries, showing differences in its distribution. In Brazil, the virus is widely disseminated throughout the herds and the few characterized isolates revealed the solely occurrence of the subgroup B. This study describes the detection and characterization of an untyped BRSV strain from a twenty-days-old calf from a herd without clinical respiratory disease. Nasal swabs were analyzed by RT-nested PCR for the F and G proteins genes. One sample has amplified the F protein gene. Sequencing and subsequent phylogenetic reconstruction were accomplished, revealing that the strain could not be grouped with any other BRSV subgroups reported. This result may suggest that the BRSV is in constantly evolution, even in Brazil, where the vaccination is not a common practice. More detailed studies about BRSV characterization are necessary to know the virus subgroups distribution among the Brazilian herds to recommend appropriated immunoprophylaxis.